Gestão de obras públicas: um estudo de caso na Universidade Federal de Santa Maria - UFSM - Bachmann, Cristiane de Paula (2017)
The present study aimed to analyze the public works management process and identify barriers that may compromise the success of a work regarding the budget, contracts management, planning and control of public works. In this sense, a documentary research, with on-the-spot observation and interviews with managers from UFSM. The results indicated that the obstacles pointed are assigned to planning failures, insufficient supervision, the precariousness of the projects or even the inadequacy of organizational structures of the agencies and entities responsible for the procurement and implementation of public works. All of these factors often result in stoppage of works, which penalizes the society in various ways: imposes losses of goods and services already performed, either by bad weather or depredations, and increases the final cost of the works as a result of the extension of the implementation period, mobilizations and finance charges not provided for originalment.